The Relationship between Identity Styles with Religious Orientation among the Students of Kashan University - Fariborz Sedighi Arfaee (University of Isfahan, 2021)
Introduction This study aims to anticipate religious orientation based on identity styles among students of Kashan University. Identity, on the one hand, distinguishes between "I" and "we" or "other" and "others", and on the other hand, it is the most important source of recognizing emotions and feelings and organizing individual and collective behaviors within the surrounding society. By integrating different aspects of identity, Berzonsky (1992) presents a process model of identity in which he uses and analyzes identity as a cognitive structure, specific framework, and source for the interpretation of experiences. His model emphasizes the various strategies for information processing that individuals use to explore issues of identity, including politics, religion, and social relations. Besides, according to Allport and Ross's (1967) theory, the religious orientation of individuals is classified into intrinsic and extrinsic categories. Intrinsic religion has become an all-encompassing religion with organized and internalized principles. In people with an intrinsic religious orientation, religion creates a sense of comfort, security, usefulness, and self-compatibility. In other words, people with religious orientation live in harmony with their religious beliefs and rituals, and this leads to greater social security and stability in them. Extrinsic religion, on the other hand, is an external tool used to satisfy one's materialistic needs, such as wealth, status, and security. With such an approach, the present study seeks to answer the question of the extent to which students’ religious orientation can be explained and predicted based on different identity styles of individuals.   Material & Methods Based on the subject under study, the method of the present research is survey and, 150 undergraduate students of Kashan University with an average age of 21.86 years, and a standard deviation of 2.24 years were selected using the convenience sampling method to test the objectives and hypotheses of the research. In the present study, the data collection method was a questionnaire and the students answered a questionnaire including a list of identity styles (ISI-G6) (based on the study of Berzonsky, 1992) and a religious orientation scale (based on the study of Allport & Ross, 1967). Discussion of Results & Conclusions Enter method in multiple regression was used to analyze the data. The findings showed that informational and normative identity styles directly and diffuse-avoidant style inversely can significantly predict intrinsic religious orientation (P=0/001, F(3 and 146)=28/29, R2=0/368). Extrinsic religious orientation was also predicted inversely and meaningfully through informational and normative styles (P=0/001, F(3 and 146)=48/71, R2=0/50). Explaining the role of informational identity in predicting intrinsic religious orientation, it can be said that people with informational identity structure their lives around their religion. Therefore, to achieve this kind of religious orientation, one needs extensive and comprehensive meditation in all aspects of life and it cannot be achieved without searching and thinking. Moreover, according to the normative identity style, individuals are constantly internalizing the expectations and value of their important others and may have internalized religion as well, despite little exploration. They avoid looking at it superficially and instrumentally. Besides, in explaining the role of avoidant identity style in predicting intrinsic religious orientation in reverse, it can be said that people with avoidant identity style interpret the content of religion superficially and avoid examining personal issues in religious affairs. In general, based on the findings of the present study, different styles of identity can explain 37% of the variance of intrinsic religious orientation and 50% of the variance of extrinsic religious orientation of the studied students. These findings, in line with the findings of some other studies, confirm the close relationship between identity and religion in young people and emphasize that in examining students' religious orientation, special attention should be paid to their identity styles.